Konsep, Urgensi dan Strategi Pembangunan Literasi Digital - Giroth, Lady Grace Jane; Purnomo, Kharies Dwi Manossoh; Dotulong, Fernando; Mokoginta, Deyidi; Pusung, Piet Hein (Puslitbang Akademi Relawan TIK Indonesia, 2024)
This article aims to describe the results of a review of various scientific articles that discuss the concept and urgency of digital literacy and formulate digital literacy development strategies. The method used in this article is the literature study method. Overall, digital literacy is a multidimensional concept that affects various aspects of community life, education, business and personal well-being. Digital literacy equips individuals with the competencies and skills necessary to navigate the digital landscape effectively, critically and ethically. As technology evolves, the evolution of digital literacy underscores the importance of continuously updating digital skills and competencies. Translated with DeepL.com (free version).